2018
DOI: 10.1093/mnras/sty268
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the accuracy of asteroseismic mass and radius estimates of giant stars – I. Three eclipsing systems at [Fe/H] ∼ −0.3 and the need for a large high-precision sample

Abstract: We aim to establish and improve the accuracy level of asteroseismic estimates of mass, radius, and age of giant stars. This can be achieved by measuring independent, accurate, and precise masses, radii, effective temperatures and metallicities of long period eclipsing binary stars with a red giant component that displays solarlike oscillations. We measured precise properties of the three eclipsing binary systems KIC 7037405, KIC 9540226, and KIC 9970396 and estimated their ages be 5.3 ± 0.5, 3.1±0.6, and 4.8±0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
100
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 59 publications
16
100
1
Order By: Relevance
“…6 (bottom panel) in Brogaard et al (2018) reveals that the same value for f ∆ν is not found if one uses T eff as reference to determine f ∆ν instead of ν max , as in Rodrigues et al (2017), even if everything else is unchanged. This may be caused by a too low temperature scale for the models used by Rodrigues et al (2017), as also discussed by Brogaard et al (2018). Retaining the view from Brogaard et al (2018) that it is better to use ν max than T eff to estimate f ∆ν , we find evidence based on our empirical correction factor pointing to the RGB as the present evolutionary phase of ǫ Tau.…”
Section: Physical Parameters and Evolutionary Statusmentioning
confidence: 69%
“…6 (bottom panel) in Brogaard et al (2018) reveals that the same value for f ∆ν is not found if one uses T eff as reference to determine f ∆ν instead of ν max , as in Rodrigues et al (2017), even if everything else is unchanged. This may be caused by a too low temperature scale for the models used by Rodrigues et al (2017), as also discussed by Brogaard et al (2018). Retaining the view from Brogaard et al (2018) that it is better to use ν max than T eff to estimate f ∆ν , we find evidence based on our empirical correction factor pointing to the RGB as the present evolutionary phase of ǫ Tau.…”
Section: Physical Parameters and Evolutionary Statusmentioning
confidence: 69%
“…We only extracted the correction values f ∆ν from the models, and used the seismic parameters and temperature values from our original set, and not the results for these values returned from the grids, in the rest of this work. We did not include corrections for the ν max scaling relation, because these are more difficult to obtain theoretically (Belkacem et al 2011), and are probably negligible (Brogaard et al 2018). Note that Brogaard et al (2018) found that using corrections by Rodrigues et al (2017) delivers on average slightly smaller stellar properties than using due to differences in how these methods treat the solar surface effect.…”
Section: Obtaining the Seismic Samplementioning
confidence: 99%
“…We did not include corrections for the ν max scaling relation, because these are more difficult to obtain theoretically (Belkacem et al 2011), and are probably negligible (Brogaard et al 2018). Note that Brogaard et al (2018) found that using corrections by Rodrigues et al (2017) delivers on average slightly smaller stellar properties than using due to differences in how these methods treat the solar surface effect. Since we used a wide range of bolometric corrections for various temperature perturbations, the method by Rodrigues et al (2017) would be too computationally expensive, and we thus elected to use , which may lead to differences of the order of ∼ 2% in radius than if we had used Rodrigues et al (2017) (White et al 2011).…”
Section: Obtaining the Seismic Samplementioning
confidence: 99%
“…In a similar approach as Gaulme et al (2016), Brogaard et al (2018) and Themeßl et al (2018) tested the asteroseismic masses and radii against masses and radii obtained from binary orbits for three eclipsing binary systems each (one system in overlap). Both studies found that asteroseismic scaling relations without corrections to the ∆ν scaling relations would overestimate the masses and radii.…”
Section: Validity Tests and Suggested Improvementsmentioning
confidence: 99%